Stunting prevention education at Posyandu Bintang Keluarga - Khusnul Laely; Erta Oktafiani; Dwi Handayani; Melati Ariana; Rifka Aina Usmazafi; Anik Ismawanti (Universitas Muhammadiyah Magelang, 2023)
Stunting is a health problem that is a priority for resolution in Indonesia to create quality human resources. The purpose of this community service is to find the root causes and solutions in preventing stunting for the people of Dusun Glagah I RT/RW 04/03. This activity was carried out in the form of stunting education. The results of this program are increasing partners' knowledge about the characteristics of stunting toddlers and the causes of stunting and the prevention of stunting. In addition, participants became more aware of the importance of growth and development and nutritional intake of children.